2001
DOI: 10.3386/w8655
|View full text |Cite
|
Sign up to set email alerts
|

Defined Contribution Pensions: Plan Rules, Participant Decisions, and the Path of Least Resistance

Abstract: We thank Hewitt Associates for their help in providing the data. We are particularly grateful to Lori Lucas and Jim McGhee, two of our many contacts at Hewitt. We also thank James Poterba and Olivia Mitchell for comments. Choi acknowledges financial support from a National Science Foundation Graduate Research Fellowship. Laibson and Madrian acknowledge financial support from the National Institute on Aging (R01-AG-16605 and R29-AG-013020 respectively). Laibson also acknowledges financial support from the MacAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
280
2
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(321 citation statements)
references
References 20 publications
28
280
2
11
Order By: Relevance
“…In many cases, these firms have introduced automatic enrolment to comply with the Internal Revenue Service's non-discrimination rules 2 (see Choi et al (2002) and Butrica and Karamcheva (2015)). …”
Section: Introductionmentioning
confidence: 99%
“…In many cases, these firms have introduced automatic enrolment to comply with the Internal Revenue Service's non-discrimination rules 2 (see Choi et al (2002) and Butrica and Karamcheva (2015)). …”
Section: Introductionmentioning
confidence: 99%
“…Suggestions to increase savings Individuals have been described as exhibiting irrationality and a severe lack of self-control, as refl ected in their fi nancial decisions, such as saving for retirement. 5,32 -34 This circumstance is extremely evident in Choi et al ' s report 35 in which he found that in a subsequent 4-month review, a massive 86 per cent of employees with the intention to increase their saving failed to do so. Therefore, it highlighted the lack of willpower to save more.…”
Section: Knowledge About Retirement Planningmentioning
confidence: 90%
“…Of the respondents saving too little, 15 per cent stated that they plan to increase their savings in the future. Choi et al 35 found that individuals severely lacked the willpower to follow through on their intentions to save more. Furthermore, only a trivial portion (1.4 per cent) indicated distrust towards pensions.…”
Section: Yes or Nomentioning
confidence: 99%
“…Several papers (surveyed in Poterba et al, 1996) found that these plans tend to increase savings among plan 9 See Laibson et al (1998). 10 See Madrian and Shea (2001), Choi et al (2001Choi et al ( , 2004a. 11 In a previous draft of this paper, we also utilized data from the 2008 wave of the SIPP.…”
Section: Related Literaturementioning
confidence: 99%